Pengaruh Pengetahuan Kewirausahaan dan Efikasi Diri Terhadap Minat Berwirausaha Pada Gen-Z Kabupaten Dairi - Sagala, Dandi; Siregar, Dahrul; Siregar, Muhammad Yamin (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
The purpose of this study was to determine the partial effect of entrepreneurial knowledge on entrepreneurial interest, to determine the partial effect of self-efficacy on entrepreneurial interest and to determine the simultaneous effect of entrepreneurial knowledge and self-efficacy on entrepreneurial interest in Gen-Z in Dairi Regency. The population in this study was generation Z in Simallopuk Village with a total of 1,688 people. The sample in the study was 94 people taken using the slovin formula. The data collection technique used in this study was carried out by distributing questionnaires. The analysis technique used in this study was multiple linear regression, partial test (t-test), simultaneous significance test (F-test) and coefficient of determination. The results of the study showed that there was an effect of entrepreneurial knowledge on entrepreneurial interest, there was an effect of self-efficacy on entrepreneurial interest and there was an effect of entrepreneurial knowledge and self-efficacy on entrepreneurial interest in Gen-Z in Dairi Regency